2022
DOI: 10.3390/v14071488
|View full text |Cite
|
Sign up to set email alerts
|

Arboviral Infections in Neurological Disorders in Hospitalized Patients in São José do Rio Preto, São Paulo, Brazil

Abstract: Arbovirus infections are increasingly important causes of disease, whose spectrum of neurological manifestations are not fully known. This study sought to retrospectively assess the incidence of arboviruses in cerebrospinal fluid samples of patients with neurological symptoms to inform diagnosis of central and peripheral nervous system disorders. A total of 255 cerebrospinal fluid (CSF) samples collected from January 2016 to December 2017 were tested for dengue virus (DENV 1-4), Zika virus (ZIKV), and Chikungu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Retrospective harmonization is generally resource-intensive (29,30), as we can attest to. In order to facilitate future IPD-MAs, we are in the process of creating a Case Report Form which we then standardized according to the CDISC data standard.…”
Section: Figure 2 Harmonization Potentialmentioning
confidence: 99%
“…Retrospective harmonization is generally resource-intensive (29,30), as we can attest to. In order to facilitate future IPD-MAs, we are in the process of creating a Case Report Form which we then standardized according to the CDISC data standard.…”
Section: Figure 2 Harmonization Potentialmentioning
confidence: 99%
“…Generalmente, el cuadro neurológico aparece temprano en el curso de la infección (incluso en el primer día de la enfermedad) y coincide con la fase virémica, aunque en la mayoría de los casos aparece entre 2 y 30 días después de la aparición del cuadro febril (10) . Otras manifestaciones neurológicas, como déficit motor, pueden ocurrir en la infección aguda (mielitis y miositis) o durante la etapa posterior al dengue (polirradiculoneuritis, encefalomielitis, neuromielitis óptica, polineuropatía y mononeuropatía) (13,14) . El diagnóstico durante el embarazo puede ser difícil, por lo que deben considerarse los cambios fisiológicos del embarazo, complicaciones relacionadas a este y otros trastornos médicos junto a los resultados de laboratorio.…”
Section: Discussionunclassified
“…Neuroimaging is not specific. 51,52 Cerebrovascular disease Rare cases have been described of ischemic and hemorrhagic stroke. 52 Previous studies have demonstrated that endothelial cells of the blood-brain barrier are permeable to ZIKV infection and replication, and they may penetrate the endothelium, causing neuronal tissue damage.…”
Section: Encephalitismentioning
confidence: 99%
“…51,52 Cerebrovascular disease Rare cases have been described of ischemic and hemorrhagic stroke. 52 Previous studies have demonstrated that endothelial cells of the blood-brain barrier are permeable to ZIKV infection and replication, and they may penetrate the endothelium, causing neuronal tissue damage. Considering that Zika has tropism and may infect endothelial cells, as demonstrated in animal models, and due to its phylogenetic relationship to DENV it is reasonable to admit a correlation between this ZIKV and strokes or brain hemorrhage.…”
Section: Encephalitismentioning
confidence: 99%
See 1 more Smart Citation